Representasi Nilai Pendidikan dalam Novel Api Tauhid: Cahaya Keagungan Cinta Sang Mujaddid Karya “Habiburrahman El-Shirazy” - Syafrizal; Cut Nabilla Kesha; Siti Jahria Sitompul; Desi Marlizar (Indonesian Journal of Teaching and Teacher Education, 2023)
This research is based on a theoretical concept that views literature as a medium for realizing educational values ​​for every community group. The research objective is to describe the educational values ​​contained in the novel. This research uses a structural approach with a descriptive research type. Data collection uses documentary techniques. Data analysis was carried out with the following steps: (1) carefully reading the novel which was the object of research; (2) noting the parts of the novel in the form of words, phrases, sentences, expressions and statements that contain educational values; (3) classifying the data based on the types of educational values ​​contained in the novels read; and (4) describe educational values. The results of the study show that the educational values ​​contained in the novel Api Tauhid: Cahaya Keagungan Cinta Sang Mujaddid are (1) the value of honesty, (2) love of peace, (3) the spirit of nationalism, and (4) the value of appreciating achievement. These four values ​​are categorized as educational values ​​because they contain teachings that form the basis of the ideals of the Indonesian nation in general which are integrated through various educational institutions, both formal and non-formal, as well as various literary works such as novels.